1971
DOI: 10.1002/ijc.2910080212
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of two distinct components in the early antigen complex of epstein‐barr virus‐infected cells

Abstract: Examination of numerous sera from patients with infectious mononucleodis ( I M ) , Burkitt 's lymphoma ( B L ) or nasopharyngeal carcinoma ( N P C ) for antibodieh to Epstein-Barr virus ( E B V ) induced early antigens ( E A ) revealed two distinct patterns of immunofluorescence in abortively E B V-infected Raji cells. One showed diguse ( D ) staining of the nucleus and cytoplasm of invaded cells, the other ( R ) was restricted to masses in the cytoplasm. Although D-or R-reactive Raji cells became detectable a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
125
0
1

Year Published

1977
1977
1986
1986

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 331 publications
(130 citation statements)
references
References 21 publications
4
125
0
1
Order By: Relevance
“…The sera used by Mueller-Lantzsch et al (1979) may have contained antibodies against a subset of the EA complex. This contention is supported by our unpublished observation that not all EA+VCA + sera precipitate the full spectrum of EA proteins, and by the observations of Henle et al (1971) who demonstrated that sera derived from patients with different EBV-induced diseases have different specificities against subcomponents of the EA complex in the fluorescent antibody staining test. From the data presented it is apparent that the regulation of EBV-induced protein synthesis is complex and a classification into primary, secondary and tertiary phases by experiments using CH inhibition is certainly not detailed enough.…”
Section: Discussionmentioning
confidence: 53%
“…The sera used by Mueller-Lantzsch et al (1979) may have contained antibodies against a subset of the EA complex. This contention is supported by our unpublished observation that not all EA+VCA + sera precipitate the full spectrum of EA proteins, and by the observations of Henle et al (1971) who demonstrated that sera derived from patients with different EBV-induced diseases have different specificities against subcomponents of the EA complex in the fluorescent antibody staining test. From the data presented it is apparent that the regulation of EBV-induced protein synthesis is complex and a classification into primary, secondary and tertiary phases by experiments using CH inhibition is certainly not detailed enough.…”
Section: Discussionmentioning
confidence: 53%
“…That sera contain antibodies against different subsets of the EA complex was first reported by Henle et al (1971), who classified EA antigens into EA-R and EA-D subcomponents. The present results, however, indicate that sera may contain antibodies reactive against select individual components of the EA-R and EA-D complexes.…”
Section: Discussionmentioning
confidence: 86%
“…These antigens were originally defined by indirect immunofluorescence procedures and have been termed viral capsid antigens (VCA), membrane antigens (MA) and early antigens (EA) (Pearson, 1980). EA can be subdivided into two distinct staining patterns: a diffuse (D) pattern detectable in both the nucleus and cytoplasm and a restricted (R) pattern localized in the cytoplasm (Henle et al, 1971). Expression of EA has been shown to be independent of DNA synthesis (Gergely et al, 1971) and can be distinguished from late viral products if cells are induced in the presence of a DNA inhibitor.…”
Section: Introductionmentioning
confidence: 99%
“…Infection of cells by P3HR-1 virus was performed according to Henle et al (9) and has been described in detail (7). Differpntiation of R-and D-subspecificities of the EA complex followed the procedures described by Henle et al (10).…”
mentioning
confidence: 99%